The Effect of Enterprise Risk Management, Intellectual Capital, and Corporate Policy Disclosure on Company Value with Good Corporate Governance as a Moderation Variable - Tampubolon, Sylvana Noviakusuma (Universitas Syiah Kuala, 2024)
This study aims to test and empirically prove the effect of Enteprise Risk Management, Intellectual Capital, and Dividend Policy on Firm Value with Good Corporate Governance as a moderating. The source of this study data uses secondary data from companies available at SP Capital IQ with a total of 141 observations that have met the criteria used using purposive sampling techniques. This study employed quantitative research by using multiple regression analysis with a moderating effect (Moderated Regression Analysis) with the STATA program. The results of the study showed that Enterprise Risk Management had negative influence on firm value, Company policy, namely dividend policy, had positive effect on firm value, and Inttelectual Capital also Good Corporate Governance had no effect on firm value. The study also showed that Good Corporate Governance as a moderating variable strengthens the relationship between company policy, namely dividend policy, on firm value but Good Corporate Governance cant moderate the relationship between both Enterprise Risk Management and Intellectual Capital on firm value.